ANALISIS KESULITAN BELAJAR MATEMATIKA PADA MATERI TRIGONOMETRI TINGKAT SMA/SMK - Usman Mulbar; Kasmawati (Afore : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the learning difficulties in mathematics specifically in the topic of trigonometry at the senior high school (SMA/SMK) level. The background of the study highlights that abstract concepts such as sine, cosine, tangent functions, identities, and equations often pose challenges for students. These difficulties are largely caused by a lack of basic geometric understanding, limited ability to visualize angles, and a curriculum that is not fully adaptive to students’ learning needs. The absence of these foundational skills makes it challenging for students to relate trigonometric concepts to real-life contexts, thereby reducing the effectiveness of learning. The research method employed is a secondary literature analysis from various reliable sources, including case studies, student surveys, and evaluations of the national curriculum. This approach enables the identification of patterns of learning difficulties qualitatively while also examining factors that influence students’ comprehension levels. The analysis results indicate that the main challenges include understanding abstract concepts (42%), applying formulas (35%), and learning motivation (23%). External factors, such as conventional teaching methods that lack variety and limited learning resources, further exacerbate the problem. Based on these findings, the study recommends innovative learning approaches, such as the use of digital technology, interactive media, and project-based learning relevant to everyday life. These approaches are expected to enhance student understanding, encourage active engagement, and reduce achievement gaps. This research aims to provide practical contributions for educators and policymakers to improve the effectiveness of trigonometry instruction at the senior high school level.